PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS ALAM DALAM RANGKA MENGEMBANGAN KOGNITIF ANAK PADA KELOMPOK B PAUD NURULZULAM - Ratnaningsih, Yayah; Arifudin, Opan; Chusnarin Haryanti, Heny (Penerbit Lafadz Jaya, 2026)
The purpose of this study is to help children improve their cognitive abilities using nature-based media. Classroom Action Research (CAR) is a two-cycle research methodology. The research approach is divided into four series of actions that take place in each cycle: planning, action implementation, observation, and reflection. This research is a collaboration between the researcher and the classroom teacher. The data for this study are based on observations, field notes, and recordings of children's cognitive capacities using nature-based media. This study involved instructors, namely seven children from Group B of Nurulzullam PAUD in Cicangor Village. The data analysis technique includes a comparative approach, which compares children's general abilities with targeted indicators for each cycle. The findings of this study imply that nature-based media improves children's cognitive capacities. Children's cognitive capacities increased by 30% in the pre-cycle, 40% in cycle I, and 50% in cycle II. This study concludes that diverse learning using nature-based media is very important for children's cognitive development at Nurulzullam PAUD in Cicangor Village.